Capture-Recapture Analysis in Estimating Tuberculosis Notification Rates in Private Healthcare Sector: An Innovative Approach to Disease Control - Suryanti, Suryanti; Ahmed, Idris Adewale (Holistic Nursing Plus, 2024)
Background: Tuberculosis (TB) is a leading global cause of death, surpassing HIV before the COVID-19 pandemic (WHO, 2022). In 2022, TB claimed 1.3 million lives globally, with Indonesia ranking second in pulmonary TB cases after India and ahead of China. WHO estimated 10.6 million new TB cases in 2022, marking a 0.3 million increase from the previous year. Without proper treatment, TB's mortality rate reaches 50% within the first year (WHO, 2023). The increasing TB burden reflects failures in control efforts, attributed to organizational shortcomings, limited community access to diagnosis and treatment, inconsistent case identification and diagnosis, inadequate drug supply guarantees, and non-standardized TB reporting, supervision, and monitoring practices. Purpose: The objective of this study is to estimate tuberculosis (TB) notifications using the capture-recapture analysis method. Methods: This study employs capture-recapture analysis as its methodology. Results: Patient records from both healthcare facilities initially showed 93 confirmed TB cases. Following detailed matching of multiple identifiers such as name, age, date of birth, place of birth, address, and National Identity Number (NIK), it was found that six patients were diagnosed at both institutions, indicating data redundancy. To refine these findings and address potential under-reporting, capture-recapture analysis estimated 320 TB cases in the population, significantly higher than reported in the Integrated Tuberculosis Information System (SITT), revealing a 25.98% discrepancy. Conclusions: Capture-recapture analysis in this study offers deeper insights into Semarang City's TB burden and prompts systemic improvements in case recording and management. By identifying reporting discrepancies and advocating for enhanced surveillance, this research supports more effective public health interventions, promising better health outcomes and a clearer understanding of TB's urban impact. This underscores the importance of collaborative efforts and a multifaceted approach integrating advanced statistical techniques and policy reforms to address this critical public health challenge.